Development of rapid guidelines: 2. A qualitative study with WHO guideline developers - Ivan D. Florez; Rebecca L. Morgan; Maicon Falavigna; Sérgio C. Kowalski; Yuan Zhang; Itziar Etxeandia-Ikobaltzeta; Nancy Santesso; Wojtek Wiercioch; Holger J. Schünemann (BMC, 2018)
Abstract Background Situations such as public health emergencies and outbreaks necessitate the development and publication of high-quality recommendations within a condensed timeframe. For example, WHO has produced examples of and guidance for the development of rapid guidelines (RGs). However, more information is needed to understand the experiences and perceptions of guideline developers. This is the second of a series of three articles addressing methodological issues around RGs. This study describes the perceptions and experiences of guideline developers at WHO about RGs. Methods We conducted interviews consisting of open- and closed-ended questions with guideline developers at WHO. Our analysis described the definition and rationale of RGs, the differences from regular guidelines with regard to timelines from topic definition until publication, barriers to identifying the evidence and the lack of a standard methodology to develop RGs. Results We interviewed 10 participants, the majority of whom were comfortable with the current WHO definition of RGs. Most stated that the rationale for developing RGs should be in response to new evidence about efficacy, cost-effectiveness or safety. Respondents differed with regards to the amount of time RGs should take. While the majority of participants agreed that guidelines should be based on a systematic review, this step in the process was considered the most time and resource intensive. Challenges for developing RGs included limited personnel and financial resources as well as the lack of evidence. Facilitators, in turn, that may improve RG development include additional financial and personnel resources as well as the use of virtual meetings. Conclusions While our study suggests a strong need and rationale for the development of RGs, standardisation of timelines and guidance on panel composition, peer-review process, conduct of meetings and sources of permissible evidence require further research.